Environmental Behavior Analysis for Electronic Waste Management in Selected Saudi Cities: A Field Exploratory Study in the Light of the Circular Economy (The International Journal for Scientific Research, 2026)
This exploratory field study analyzes individuals' environmental behavior toward e-waste management in selected Saudi cities in light of the circular economy. Using a descriptive-analytical design grounded in the Theory of Planned Behavior, an online questionnaire was administered to a convenience sample of 68 participants, and the data were analyzed with SPSS through descriptive statistics, chi-square tests, and Spearman correlation. The results show that 54.4% of participants store old devices at home, only 7.4% deliver them to certified recycling facilities, and 86.8% are unaware of official collection points. Significant associations were found between spatial knowledge and disposal behavior (p = 0.002), risk awareness and willingness to deliver devices (p = 0.009), and financial incentives and delivery readiness (p = 0.031). The study recommends integrating collection-point maps into government digital applications, expanding fixed and mobile collection infrastructure, strengthening targeted awareness campaigns, and developing incentive-based return programs. It proposes a three-dimensional explanatory framework combining institutional, spatial, and behavioral structures, while emphasizing that the findings are exploratory and should be tested with larger representative samples.
Keywords: e-waste; environmental behavior; circular economy; spatial knowledge; waste management; Saudi Arabia; financial incentives